PROBLEMS OF FORECASTING FLOODS AND FLOODING - Leonid Alekseevich Afonin (Наука. Инновации. Технологии)
The article draws attention to the fact that floods take place every year in Russia and some of them bring a huge damage to the country. Their reliable prediction requires timely determine of the amount and timing of rain and streams of power and speed channel flow throughout the river. Questions of improving the accuracy of measurement of these parameters are discussed